Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi pada KPPN Surabaya I dan KPPN Surabaya II) - Nuryadi, Deddi (TEMA, 2020)
Changes in today's business environment demand every organization to be able to adapt by giving the best service to its customers. Public sector organizations are also doing services improvement that aims to improve the performance of the ongoing transformation process, which is important factor in improving the performance focused on transformational leadership, organizational culture and job satisfaction. The objective of this research is to determine the effect of transformational leadership and organizational culture on employee performance with the mediation of job satisfaction. The study was conducted by using primary data collected by questionnaire distributed to all employees of KPPN Surabaya I and KPPN       Surabaya II. The data have been collected and then analyzed using SEM PLS with SmartPLS 3.0 Program. Results from this study are: 1) transformational leadership and organizational culture have a significant effect on employee performance; 2) Transformational leadership and organizational culture have a significant effect on job satisfaction; 3) job satisfaction does not significantly influence employee performance; 4) job satisfaction does not become mediation between transformational leadership and organizational culture on employee performance. Keywords: Transformational Leadership, Organizational Culture, Job Satisfaction, and Employee Performance.